'To Beijing and Back': Reflections on the Influence of the Beijing Conference on Popular Notions of Women's Empowerment in Ghana. (July 2015) - Manuh, Takyiwaa; Anyidoho, Nana Akua
Abstract The 1995 Fourth World Conference on Women in Beijing was a pivotal moment for legitimating women's rights work in Ghana and served as a powerful framing for women's empowerment. This article explores the Beijing conference and examines its influence on popular notions of and efforts to promote women's empowerment. We argue that the discursive context provided by the conference shaped popular narratives about women directly and also through its influence on the ideas and practices of public institutions and civil society. There is greater acceptance that women have rights that should be promoted and protected, and that there should be institutions and systems to which they have recourse. However, significant work remains to be done in tackling the resistances and tokenism that continue to dominate public discourses and actions to advance gender equality. Further efforts to advance women's empowerment and gender equality in Ghana must therefore build on the legacy of the Beijing conference.